Student pharmacist initiated medication reconciliation in the outpatient setting - Andrus MR (Centro de Investigaciones y Publicaciones Farmaceuticas, 2012)
The Joint Commission continues to emphasize the importance of medication reconciliation in all practice settings. Pharmacists and student pharmacists are uniquely trained in this aspect of patient care, and can assist with keeping accurate and complete medication records through patient interview in the outpatient setting.Objective: The objective of this study was to quantify and describe medication reconciliation efforts by student pharmacists in an outpatient family medicine center.Methods: A retrospective review was conducted of all standard medication reconciliation forms completed by student pharmacists during patient interviews from April 2010 to July 2010. The number of reviews conducted was recorded, along with the frequency of each type of discrepancy. A discrepancy was defined as any lack of agreement between the medication list in the electronic health record (EHR) and the patient-reported regimen and included any differences in dose or frequency of a medication, duplication of the same medication, medication no longer taken or omission of any medication.Results: A total of 213 standard medication forms from the 4 month period were reviewed. A total of 555 discrepancies were found, including medications no longer taken, prescription medications that needed to be added to the EHR, over-the-counter(OTC) and herbal medications that needed to be added to the EHR, medications taken differently than recorded in the EHR, and medication allergies which needed to be updated. An average of 2.6 discrepancies was found per patient interviewed.Conclusion: Student pharmacist-initiated medication reconciliation in an outpatient family medicine center resulted in the resolution of numerous discrepancies in the medication lists of individual patients. Pharmacists and student pharmacists are uniquely trained in medication history taking and play a vital role in medication reconciliation in the outpatient setting.